Control of foreign Ag‐specific Ab responses by Treg and Tfr. Issue 1 (20th June 2020) - Wing, James B.; Lim, Ee Lyn; Sakaguchi, Shimon
Abstract: Regulatory T cells (Tregs) expressing the transcription factor Foxp3 play a critical role in the control of immune homeostasis including the regulation of humoral immunity. Recently, it has become clear that a specialized subset of Tregs, T‐follicular regulatory cells (Tfr), have a particular role in the control of T‐follicular helper (Tfh) cell‐driven germinal center (GC) responses. Following similar differentiation signals as received by Tfh, Tfr gain expression of characteristic chemokine receptors and transcription factors such as CXCR5 and BCL6 allowing them to travel to the B‐cell follicle and deliver in situ suppression. It seems clear that Tfr are critical for the prevention of autoimmune antibody induction. However, their role in the control of foreign antigen‐specific antibody responses appears more complex with various reports demonstrating either increased or decreased antigen‐specific antibody responses following inhibition of Tfr function. Due to their recent discovery, our understanding of Tfr formation and function still has many gaps. In this review, we discuss our current knowledge of both Tregs and Tfr in the context of humoral immunity and how these cells might be manipulated in order to better control vaccine responses.